EKSISTENSI SMP NEGERI 9 PARIAMAN DI DESA MARUNGGI KECAMATAN PARIAMAN SELATAN (2006-2015) - Nora, Silvia; Ibrahim, Bedriati; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Education is one of the most important in life. In addition to being one of the benchmarks or not a country, education also plays an important role in the survival. SMPN 9 Pariaman is the youngest educational institutions in the city of Pariaman, although it has been operating for nine years but there are many rapid educational development in South Pariaman District. The purpose of this research is: (1) To know the history of SMPN 9 Pariaman in the Marunggi village of Pariaman South subdistrict (2006). (2) to know the developments in SMP Negeri 9 in marunggai Village Pariaman South subdistrict (2006-2015). (3) To know SMPN 9 pariaman Achievement in marunggai Village South Pariaman subdistrict. (4) To know the efforts made to maintain the existence of SMP Negeri 9 Pariaman. In this research method approach in which data are collected through the Library Study of History, Interview and Documentation. Analysis of data using qualitative approach. When the study started from the filing of the title until the end of last revision writer. the Results showed there was an attempt to maintain the existence of SMPN 9 Pariaman to promote the development of education in the marunggi village south pariaman subdistrictKeyword: Existence, SMPN 9 Pariaman